Fumantes sintomáticos sem DPOC com suspeita de doença microvascular pulmonar associada ao tabaco e tratamento com Sildenafila: um estudo cruzado, duplo-cego e randomizado - Goelzer, Leandro Steinhorst (2022)
CONTEXT: Symptomatic smokers without chronic obstructive pulmonary disease (COPD) are at increased risk of mortality and rapid decline in lung function, with significant exercise intolerance. Pulmonary microvascular disease (PMD) emerges as a potential mechanism for dyspnea in this group. It is also known that sildenafil has a pulmonary and peripheral vasodilation effect. OBJECTIVE: To characterize a clinical-functional phenotype of PMD and to evaluate the potential beneficial effects of sildenafil in symptomatic smokers without COPD, with suspected PMD, having as primary objective the maximum time of tolerance to physical exercise (Tlim, s). As secondary objectives, (i) the kinetics of adjustment of pulmonary oxygen consumption (τ⩒O2) and (ii) the kinetics of deoxyhemoglobin τ[HHb] by oxygen extraction in the vastus lateralis muscle during cardiopulmonary exercise tests (CPET). METHODS: A double-blind, randomized, placebo-controlled crossover trial. Thus, 24 volunteers, divided into a smoker group (SG) and another control group (CG): SG (16 individuals with suspected PMD) and CG (8 individuals without exposure to smoke) underwent two CPET with constant load at 75% of the maximum load in the incremental CPET, randomly. Each test was preceded by the administration of sildenafil (50 mg) or placebo orally one hour before exercise. Metabolic monitoring for τ⩒O2 and τ[HHb] were performed by cardiometabolic system and near infrared spectroscopy (NIRS), respectively. RESULTS: No difference between groups and treatment for Tlim, τ⩒O2 and τ[HHb]. CONCLUSION: In symptomatic smokers without COPD, sildenafil had no effect on Tlim, the τ⩒O2 and the τ[HHb] in the vastus lateralis muscle. It was not possible to validate a proposed DMP phenotype with a vasodilator, but the suggestion remains as a potential diagnostic tool (ReBEC RBR-9t6rd7). Descriptors: sildenafil citrate; exercise; smokers; microvascular rarefaction.